Optimizing High-Load Systems with Asynchronous Programming Techniques - Самойдюк, Андрій; Остапчук, Оксана (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
This document focuses on a critical issue in modern application - performance. The goal is to find the best way to improve the efficiency of these systems, with a particular focus on smart home management applications. As the popularity of such systems grows rapidly, enhancing their performance is becoming necessary. To address this need to explore existing challenges and evaluates various solutions. The proposed asynchronous programming approach to solve the listed problems. Performance tests showed the efficiency of this method in comparison with other approaches.